Novel taxa of thermally dimorphic systemic pathogens in the Ajellomycetaceae (Onygenales). Issue 5 (7th February 2017) - Dukik, Karolina; Muñoz, Jose F.; Jiang, Yanping; Feng, Peiying; Sigler, Lynne; Stielow, J. Benjamin; Freeke, Joanna; Jamalian, Azadeh; Gerrits van den Ende, Bert; McEwen, Juan G.; Clay, Oliver K.; Schwartz, Ilan S.; et al.
Summary: Recent discoveries of novel systemic fungal pathogens with thermally dimorphic yeast‐like phases have challenged the current taxonomy of the Ajellomycetaceae, a family currently comprising the genera Blastomyces, Emmonsia, Emmonsiellopsis, Helicocarpus, Histoplasma, Lacazia and Paracoccidioides . Our morphological, phylogenetic and phylogenomic analyses demonstrated species relationships and their specific phenotypes, clarified generic boundaries and provided the first annotated genome assemblies to support the description of two new species. A new genus, Emergomyces, accommodates Emmonsia pasteuriana as type species, and the new species Emergomyces africanus, the aetiological agent of case series of disseminated infections in South Africa. Both species produce small yeast cells that bud at a narrow base at 37°C and lack adiaspores, classically associated with the genus Emmonsia . Another novel dimorphic pathogen, producing broad‐based budding cells at 37°C and occurring outside North America, proved to belong to the genus Blastomyces, and is described as Blastomyces percursus .